An observational study of incidence of surgical site infections in gastrointestinal surgeries - Modi, Jenishkumar Vijaykumar; Kalaria, Darshit (International Surgery Journal, 2021)
Background: This study analysed the incidence of surgical site infections in gastrointestinal surgeries and its risk factors. so this study helped us in reducing surgical site infection by avoiding or minimizing that risk factors. Methods: The present study was conducted at general surgery department, SMIMER, Surat. An observational study of 400 cases that have undergone abdominal surgery in SMIMER hospital and were followed up from the day of operation to 30 days after discharge was done. Results: The overall infection rate for a total of the 400 cases was 17.25%. The incidence rate in this study was well within the infection rates of 2.8% to 17% seen in other studies. Different studies from India at different places have shown the SSI (surgical site infection) rate to vary from 6.09% to 38.7%. Conclusions: Our study reveals that though SSIs have been widely studied since a long time, they still remain as one of the most important causes of morbidity and mortality in surgically treated patients.